Inner-City Fathers of Children Affected by Chronic Illness: A Systematic Scoping Review of Their Experiences. (1st June 2016) - Kobylianskii, A; Jegathesan, T; Young, E; Fung, K; Huber, J; Minhas, R
Abstract: BACKGROUND: Childhood chronic illness often impacts not just the child but the whole family, particularly the parents. Parents from inner-city backgrounds (defined as low income/socioeconomic status, unemployed, immigrant, refugee, or ethnic minority, and living in an urban area) face additional challenges. Research has traditionally centred on the mother's role in caring for a child with a chronic illness, but with the increasing role of fathers caring for these children, research has shifted its focus on paternal experience. However, the experiences of inner-city fathers remain largely unknown. OBJECTIVES: This systematic scoping review aims to explore the experiences of fathers of children with disabilities or chronic health conditions from inner city families, using the Double ABCX model as a conceptual framework. DESIGN/METHODS: A systematic scoping review was conducted between November 2014 and January 2015 using the Arksey and O'Malley framework. Seven databases were searched (Medline, PsycInfo, Embase, Web of Science, CINAHL, Scopus, and Social Work Abstracts). Titles and abstracts meeting inclusion and exclusion criteria were included in the full text review for further assessment. Qualifying articles were critically appraised and relevant data were extracted. The Double ABCX model was used to qualitatively evaluate the articles in terms of stressors, resources, perception, coping, and adaptation. RESULTS: 5114 articles were initially identified and 14 articles met the inclusion criteria. Most of the included studies were conducted in the USA. Most articles discussed fathers from low income/SES backgrounds, while others discussed ethnic minority, immigrant/refugee, and unemployed fathers. Fathers' stressors included financial strain and barriers to accessing healthcare. Fathers' resources, or sources of support, ranged from immediate to extended family members, depending on ethnicity. In terms of perceptions, fathers had different approaches to reconciling the care-giver role with cultural gender norms. Inner-city fathers had more desire for information about their children's health, but some were uncomfortable with asking physicians. Inner-city fathers were more at risk for coping difficulties and used different coping strategies compared to higher income fathers. Inner-city fathers were at higher risk for maladaptation, including depression, PTSD and less acceptance of the child. CONCLUSION: Fathers from inner-city backgrounds caring for their children affected by chronic illnesses and disabilities have unique experiences requiring a comprehensive approach to providing and communicating care to these children and caregivers. Findings from this review can be used to guide pediatricians in advocating for resources to reduce stressors, enhance coping, and promote positive adaptation for inner-city fathers.